Effect of Boron Foliar Application on Reproductive Growth of Sunflower (Helianthus annuus L.) - M. M. Al-Amery; J. H. Hamza; M. P. Fuller (International Journal of Agronomy)
A study was carried out to determine the response of open pollinated sunflower (Helianthus annuus L. cv. Shumos) to boron fertilizer. Spring and autumn grown plots were sprayed with boron (0, 50, 100, 150, 200, and 250 mg L−1) in a randomized complete block design. The results showed that boron and green Leaf area/LAI measured at the end of seed filling were linearly related in the spring crop. In the autumn crop, the relationship between boron and dry matter yield was linear, and applications above 100 mg L−1 significantly increased dry matter compared to the control. For the autumn crop, 100, 200, and 250 mg L−1 significantly increased seed number compared to the control, but only the 150 mg L−1 treatment increased seed weight significantly. Boron tended to decrease the empty seed percentage, and for the spring crop, this was incremental and linear with applications above 150 mg L−1 leading to significant reductions in empty seed percentage. Seed yield increased linearly in the autumn crop in response to boron, and 200 and 250 mg L−1 applications gave significant increases in yield compared to the control.